“Prussian Emigrants”. Glatz-Silesian Communities in East and East-Central Bohemia (1763–1946) (Theatrum historiae, 2018)
After the Seven Years‘ War (1756–1763) a number of socalled “Prussian emigrants” arrived in Bohemia. These migrants came mainly from the County of Glatz and Silesia. Their homeland was permanently connected to Prussia, but many Catholics remained loyal to the Habsburgs. Some of them initially found their refuge in the Bohemian borderland. Later a part of them moved to Bohemian inland. Between 1780 and 1785 they founded, or participated in the founding, twelve villages near Pardubice and one settlement in the Poděbrady estate. The Germanspeaking colonists came to the purely Czech regions. The aim of this article is to analyze the course of this migration, colonization, integration and later assimilation processes that led to the decline of the German settlements by the early 20th century. Attention will be paid to the collective identity of immigrants and their descendants, their relations to the Czech surroundings, marriage strategies, demographic trends and changes in language identity. The relics of the defunct German settlements, including the fate of the last native Germanspeaker, will also be mentioned.
Keywords: migration; language enclaves; Germans; integration of migrants; assimilation; mixed marriages; German schools; Pardubice estate/region; Poděbrady estate/Nymburk region